(untitled) (Al-Academy, 2017)
Find cares studying ways in the development of industrial products and designs: the way the progressive development (how typical) and root development (jump design), was the aim of the research: to determine the effectiveness of the pattern and the jump in the development of designs and industrial products. After a process of analysis of a sample of research and two models of contemporary household electrical appliances, it was reached a set of findings and conclusions including:1-leaping designs changed a lot of entrenched perceptions of the user on how the product works and its use and the size and shape of the product, revealing him about the possibilities of sophisticated relationships with the product, while keeping the typical designs the relationship between them and the user monotonous or limited development.2-expressionist aesthetic dimension in the typical design Verifier automatically because of a deliberative design and the accumulation of experience at receiver, while the design jumper needs to methods of expression fit with the nature of the radical change he holds and is easier for the recipient to understand, taking into account the lack of experience design